2020
DOI: 10.1016/j.asmart.2019.10.002
|View full text |Cite
|
Sign up to set email alerts
|

A high glucose level stimulate inflammation and weaken pro-resolving response in tendon cells – A possible factor contributing to tendinopathy in diabetic patients

Abstract: BackgroundTendinopathy is a chronic disorder that affects a huge population, and is causing high socioeconomical impacts worldwide. Tendinopathy was reported to be more prevalent in diabetic patients, and chronic inflammation was proposed to play an important role in its development. It was also known that diabetic patients present in a pro-inflammatory state. There is a possibility that the high glucose environment in diabetic patients lead to chronic inflammation in the tendon, and eventually the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…There is accumulating evidence that inflammatory cells are present, and chronic inflammation is a feature of tendinopathy[ 85 , 86 ], especially diabetic tendinopathy[ 3 ]. Kwan et al [ 87 ] showed that the mRNA expression of COX2 was increased in both healthy and tendinopathic TSPCs under high glucose conditions, while the upregulation of FPR1, ChemR23, and ALOX15 mRNA was significantly weakened in tendinopathic TSPCs upon IL-1β stimulation compared with that of healthy TSPCs, and the upregulation of ALOX15 mRNA was also weakened in IL-1β stimulated healthy TSPCs after preincubation in a high glucose environment. These results suggest that high glucose conditions may stimulate inflammation in tendinopathy and weaken the ability of pro-resolving response in TSPCs.…”
Section: Cytological and Molecular Alterations In Tendon Stem/progenimentioning
confidence: 99%
See 1 more Smart Citation
“…There is accumulating evidence that inflammatory cells are present, and chronic inflammation is a feature of tendinopathy[ 85 , 86 ], especially diabetic tendinopathy[ 3 ]. Kwan et al [ 87 ] showed that the mRNA expression of COX2 was increased in both healthy and tendinopathic TSPCs under high glucose conditions, while the upregulation of FPR1, ChemR23, and ALOX15 mRNA was significantly weakened in tendinopathic TSPCs upon IL-1β stimulation compared with that of healthy TSPCs, and the upregulation of ALOX15 mRNA was also weakened in IL-1β stimulated healthy TSPCs after preincubation in a high glucose environment. These results suggest that high glucose conditions may stimulate inflammation in tendinopathy and weaken the ability of pro-resolving response in TSPCs.…”
Section: Cytological and Molecular Alterations In Tendon Stem/progenimentioning
confidence: 99%
“…These results not only reveal the pathological mechanisms of diabetic tendinopathy but also provide a new potential treatment strategy. Kwan et al [ 87 ] showed that high glucose conditions stimulated an inflammatory response and increased COX2 in both healthy and tendinopathic TSPCs; high glucose also weakened the pro-resolving responses, with decreased expression of FPR1, ChemR23, and ALOX15 in tendinopathic TSPCs and ALOX15 in healthy TSPCs, which may cause persistent chronic inflammation in tendinopathic tendons and increase the risk of diabetic tendinopathy. The potential mechanisms associated with TSPCs during the progression of diabetic tendinopathy are summarized in Figure 2 .…”
Section: Mechanisms Involved In Diabetic Tendinopathymentioning
confidence: 99%
“…In this context, hyperglycemia was reported to increase ROS production and mRNA expression of NADPH oxidase 1 and 4, IL-6, MMP-2, MMP-9, MM-13, TIMP-1 and TIMP-2 in tendon cells [ 107 , 108 ]. Besides, a high glucose concentration was also reported to upregulate the mRNA expression of COX-2 in healthy TDSCs and tendinopathic TDSCs [ 109 ]. The expression of ALOX15 was significantly reduced in IL-1β stimulated healthy TDSCs at a high glucose level, suggesting that the inflammation pro-resolving response of TDSCs was weakened in a high glucose environment [ 109 ].…”
Section: Common Inflammatory Mediators Linking Obesity and Tendinopathymentioning
confidence: 99%
“…In another study from Kwan and colleagues, TDSCs were isolated from tendinopathic and healthy human specimens and exposed to IL‐1β, high glucose or both. High glucose increased cyclooxygenase‐2 levels in both groups, while tendinopathic TDSCs showed a reduced expression of arachidonate lipoxygenase‐15, formyl peptide receptor‐1 and chemerin receptor‐23, which are all involved in the production of specialized pro‐resolving mediators, thus stimulating a pro‐inflammatory response 45 …”
Section: Tendinopathy and T2dmentioning
confidence: 99%